Um framework para testes de software na nuvem - Oliveira, Gustavo Sávio de (2012)
Cloud Computing infrastructures can be used to make the testing process more efficient and effective, resulting from lower costs of acquisition of infrastructure to the flexibility of using only the resources actually required to perform the tests. However, exploiting such infrastructures to assist in the testing process requires automation and setup procedures not always available. In this context, we identified the lack of tools that effectively automate the entire process and make a cloud computing infrastructure part of the development and testing environment. This work presents a solution that distributes and coordinates the parallel execution of automated software testing in distributed and heterogeneous environments. This solution, called CloudTesting, provides the necessary support to developers to perform unit tests in the cloud. Experiments performed with CloudTesting in a cloud computing infrastructure showed reductions of more than 20 hours of execution time spent of a condensed set of unit tests.